Egg Parasitoids of Dalbulus maidis (Hemiptera: Cicadellidae) Within Maize Agroecosystems and in the Edge Zones of Maize Fields, and on Maize Varieties During the Wet Season in Mexico. Issue 6 (4th December 2018) - Becerra-Chiron, Iskra M; Moya-Raygoza, Gustavo
Abstract: Little is known about Dalbulus maidis (DeLong) egg parasitoids within maize fields, in the edge zones that surround these fields, and the parasitism on D. maidis eggs oviposited on different maize varieties. The objectives of the present study were first to understand which egg parasitoid species attack D. maidis eggs within maize fields and in the surrounding edge zones, and second, to compare parasitism on two maize varieties (land race Ancho-pozolero and hybrid Tigre-Asgrow) during the maize-growing wet season. We used maize plants with sentinel eggs to attract the egg parasitoids in two consecutive wet seasons, in 2015 and 2016. In 2015, Anagrus sp. (Hymenoptera: Mymaridae) and Paracentrobia sp. (Hymenoptera: Trichogrammatidae) parasitized D. maidis eggs within the maize field and on its edges. However, much more parasitism was seen within the maize agroecosystem than in the maize edge zones. In 2016, two Mymaridae species, Anagrus columbi Perkins and Anagrus sp, and two Trichogrammatidae genera, Pseudoligosita sp. and Paracentrobia sp., attacked the D. maidis eggs laid on maize hybrids but not those oviposited on the maize land race. Our findings indicate that parasitism of corn leafhopper eggs differs with agroecosystem location and maize varieties.